Performance Regulation of Thieno[3,2-b]benzothiophene π-Spacer-Based D-π-A Organic Dyes for Dye-Sensitized Solar Cell Applications: Insights From Computational Study - Xie, Xiaoyin; Liu, Zhi-Hai; Bai, Fu-Quan; Zhang, Hong-Xing (Frontiers in Chemistry, 2019)
Dye-sensitized solar cells have been widely investigated; however, the development of promising dye sensitizers is still appealing. In this work, we perform a detailed theoretical search for high-efficiency D-π-A organic dyes using density functional theory and time-dependent density functional theory calculations. Specifically, we perform geometric optimisation, and electronic structure and absorption spectra calculations for isolated dyes for two thieno[3,2-b]benzothiophene π-spacer-based D-π-A organic dyes SGT129 and SGT130, which show significant efficiency difference, before and after binding to a TiO2 semiconductor. The calculation results reveal that the coplanar configuration between the electron donor and the π-spacer can enhance electronic communication efficiently, thus facilitating intra-molecular charge transfer from the electron donor to the acceptor groups in SGT130. The absorption spectrum of SGT130 broadens and is red-shifted owing to the decreased bandgap. The higher light-harvesting efficiency, favourable intra-molecular charge transfer, larger shift of the conduction band edge in the TiO2 semiconductor, and slower charge recombination between the injected electrons in the TiO2 conduction band and the electrolyte explain the superior efficiency of SGT130 over that of SGT129. Using SGT130 as the reference dye, we further design four novel dyes 1–4by modifying the π-spacer with electron-rich and electron-withdrawing moieties. Judging from the theoretical parameters influencing the short-circuit current and open-circuit voltage, we found that all dyes would perform better than SGT130in terms of the favourable interfacial charge transfer and light-harvesting efficiency, as well as the larger shift of the TiO2 conduction band edge. Our theoretical research is expected to provide valuable insights into the molecular modification of TBT-based D-π-A organic dyes for dye-sensitized solar cell applications.